Identification of integrons and gene cassette-associated recombination sites in bacteriophage genomes - Qi, Qin; Rajabal, Vaheesan; Ghaly, Timothy M.; Tetu, Sasha G.; Gillings, Michael R. (Frontiers in Microbiology, 2023)
Bacteriophages are versatile mobile genetic elements that play key roles in driving the evolution of their bacterial hosts through horizontal gene transfer. Phages co-evolve with their bacterial hosts and have plastic genomes with extensive mosaicism. In this study, we present bioinformatic and experimental evidence that temperate and virulent (lytic) phages carry integrons, including integron-integrase genes, attC/attI recombination sites and gene cassettes. Integrons are normally found in Bacteria, where they capture, express and re-arrange mobile gene cassettes via integron-integrase activity. We demonstrate experimentally that a panel of attC sites carried in virulent phage can be recognised by the bacterial class 1 integron-integrase (IntI1) and then integrated into the paradigmatic attI1 recombination site using an attC x attI recombination assay. With an increasing number of phage genomes projected to become available, more phage-associated integrons and their components will likely be identified in the future. The discovery of integron components in bacteriophages establishes a new route for lateral transfer of these elements and their cargo genes between bacterial host cells.